2015
DOI: 10.1002/lary.25417
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based management of the thyroid gland during a total laryngectomy

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…This ambispective review of 10 years of consecutive patients treated for squamous cell carcinoma with total laryngectomy at a single center has shown that preoperative CT is an effective method of ruling out thyroid gland invasion. The 11.29% incidence for thyroid invasion described in this study is similar to that reported in larger series; Kumar et al's large meta‐analysis reported 10.7% (95% CI: 7.6%‐14.2%) …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This ambispective review of 10 years of consecutive patients treated for squamous cell carcinoma with total laryngectomy at a single center has shown that preoperative CT is an effective method of ruling out thyroid gland invasion. The 11.29% incidence for thyroid invasion described in this study is similar to that reported in larger series; Kumar et al's large meta‐analysis reported 10.7% (95% CI: 7.6%‐14.2%) …”
Section: Discussionsupporting
confidence: 88%
“…Cartilage involvement has not been shown to be predictive of thyroid invasion, as described in other studies . However, extralaryngeal spread on CT has been shown to have a high negative predictive value and specificity, with narrow 95% CIs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous studies have demonstrated that thyroid cartilage involvement and subglottic extension are associated with tumour extension into the thyroid. 17,18 A systematic review and meta-analysis from Newcastle upon Tyne Hospitals highlighted that the relative risk of thyroid gland invasion for patients with subglottic extension was 4.3 (95 per cent CI = 2.5–7.2). 19 While our study confirms the significance of cartilage invasion, the positive predictive value remained low (less than 30 per cent), even for statistically significant associations.…”
Section: Discussionmentioning
confidence: 99%